Biotopes of the intertidal zone in Clarence Island (south of the Strait of Magellan) - Aldea Venegas, Cristian Leonardo; Hernandez, Cristina; Novoa, Leslie; Olivera, Francisco; Haeger, Christian; Bello, Nadja (My University, 2023)
Background The characteristics of the Strait of Magellan promote the formation of unique environments, with diverse habitats and marine organisms. This fragmentation of the landscape generates diverse little-explored ecological associations, especially in the zone of sub Antarctic islands of the Tierra del Fuego archipelago. One way to address this lack of knowledge is through the biotope characterization methodology, with ecological units composed of the habitat and the communities associated with these environments, obtaining data and information on the dominant and incidental taxonomic groups. This is a good research model to conduct baseline studies in coastal benthic marine environments. New information A data set in Darwin Core standard is presented of the species that make up the intertidal biotopes of Clarence Island (Tierra del Fuego Archipelago, south of the Strait of Magellan). This includes 50 identified species and the specific coordinates for each sampled location, with a total of 1400 georeferenced records. Mollusks were the most diverse taxon with 21 species, followed by algae (14 species). Sessile organisms such as the barnacles Elminius kingii and Austromegabalanus psittacus predominate in these ecosystems, followed by bivalve mollusks such as Choromytilus chorus and Mytilus chilensis, which together with Nacella magellanica and the alga Hildenbrandia sp. make up more than 50% of the total records. The inclusion of biotope patterns in this study complements the information on benthic marine flora and fauna in the intertidal zone, including new records for the coast in the Clarence Island area, which is within the boundary of the Kawesqar National Park.
Keywords: barnacles; benthos; biodiversity; darwin core; kawesqar national park; mollusks; tierra del fuego archipelago